Wave Dynamics and Composite Mechanics for Microstructured Materials and Metamaterials - Sumbatyan, Mezhlum A.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This volume deals with topical problems concerning technology and design in construction of modern metamaterials. The authors construct the models of mechanical, electromechanical and acoustical behavior of the metamaterials, which are founded upon mechanisms existing on micro-level in interaction of elementary structures of the material. The empiric observations on the phenomenological level are used to test the created models. The book provides solutions, based on fundamental methods and models using the theory of wave propagation, nonlinear theories and composite mechanics for media with micro- and nanostructure. They include the models containing arrays of cracks, defects, with presence of micro- and nanosize piezoelectric elements and coupled physical-mechanical fields of different nature. The investigations show that the analytical, numerical and experimental methods permit evaluation of the qualitative and quantitative properties of the materials of this sort, with diagnosis of their effective characteristics, frequency intervals of effective energetic cutting and passing, as well as effective regimes of damage evaluation by the acoustic methods.
Mathematical models and finite element approaches for nanosized piezoelectric bodies with uncoupled and coupled surface effects -- On the theory of acoustic metamaterials with a triple-periodic system of interior obstacles -- Analytical and computer methods to evaluate mechanical properties of the metamaterials based on various models of polymeric chains -- Identification of arrays of cracks in the elastic medium by the ultrasonic scanning -- Short-wave diffraction of elastic waves by voids in en elastic medium with double reflections and transformations -- Finite element modeling and computer design of anisotropic elastic porous composites with surface stresses -- Acceleration waves in the media with microstructure -- Models of active bulk composites and new opportunities of the ACELAN Finite Element Package -- On the models of three-layered plates and shells with thin soft core -- Ray Tracing method for a high-frequency propagation of the ultrasonic wave through a triple-periodic array ofspheres -- An experimental model of the ultrasonic wave propagation through a doubly-periodic array of defects -- Finite element simulation of thermoelastic effective properties of periodic masonry with porous bricks.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Acoustics; Acoustical engineering; Materials; Solid Mechanics; Characterization and Analytical Technique; Acoustics; Engineering Acoustics; Materials Engineering